3D microtissue–derived human stem cells seeded on electrospun nanocomposites under shear stress: Modulation of gene expression. (February 2020) - Schneider, Isabelle; Baumgartner, Walter; Gröninger, Olivier; Stark, Wendelin J.; Märsmann, Sonja; Calcagni, Maurizio; Cinelli, Paolo; Wolint, Petra; Buschmann, Johanna
Abstract: Objective: Different microenvironments trigger distinct differentiation of stem cells. Even without chemical supplementation, mechanical stimulation by shear stress may help to induce the desired differentiation. The cell format, such as three-dimensional (3D) microtissues (MTs), MT-derived cells or single cells (SCs), may have a pivotal impact as well. Here, we studied modulation of gene expression in human adipose–derived stem cells (ASCs) exposed to shear stress and/or after MT formation. Materials and methods: Electrospun meshes of poly-lactic-co-glycolic acid and amorphous calcium phosphate nanoparticles (PLGA/aCaP) at a weight ratio of 60:40 were seeded with human ASCs as MTs or as SCs and cultured in Dulbecco's modified Eagle's medium without chemical supplementation. After 2 weeks of static culture, the scaffolds were cultured statically for another 2 weeks or placed in a Bose® bioreactor with a flow rate per area of 0.16 mL cm −2 min −1 . Stiffness of the scaffolds was assessed as a function of time. After 4 weeks, minimum stem cell criteria markers and selected markers of osteogenesis, endothelial cell differentiation, adipogenesis and chondrogenesis were analysed by quantitative real-time polymerase chain reaction. Additionally, cell distribution within the scaffolds and the allocation of the yes-associated protein (YAP) in the cells were assessed by immunohistochemistry. Results: MTs decayed completely within 2 weeks after seeding on PLGA/aCaP. The osteogenic marker gene alkaline phosphatase and the endothelial cell marker gene CD31 were upregulated in MT-derived ASCs compared with SCs. Shear stress realised by fluid flow perfusion upregulated peroxisome proliferator–activated receptor gamma 2 expression in MT-derived ASCs and in SCs. The nuclear-to-cytoplasmic ratio of YAP expression was doubled under perfusion compared with that under static culture for MT-derived ASCs and SCs. Conclusions: Osteogenic and angiogenic commitments were more pronounced in MT-derived ASCs seeded on bone biomimetic electrospun nanocomposite PLGA/aCaP than in SCs seeded without induction medium. Furthermore, the static culture was superior to the perfusion regimen used here, as shear stress resulted in adipogenic commitment for MT-derived ASCs and SCs, although the YAP nuclear-to-cytoplasmic ratio indicated higher cell tensions under perfusion, usually associated with preferred osteogenic differentiation.